A study of the copepods of the inshore waters of Palk Bay and Gulf of Mannar - Krishna Kartha, K N (Indian Journal of Fisheries, 2016)
It has been reported by Prasad (1956) that the general trends in the fluctuations of the total copepods, including copepodites, in the Gulf of Mannar and Palk Bay were different. According to him the fluctuations were apparently dicyclic at station G in the Gulf of Mannar, with one peak during December-March and another during September or October, as against the fluctuations at station P in Palk Bay, starting from a very low level and almost continuously increasing until it reached a maximum in September or October and then declining. In order to study the causes which bring about these differences in the population of copepods at the two stations it was suggested that a detailed analysis of the composition of population and the behaviour of the dominant species be taken up.